"Exposure to respirable crystalline silica during five OSHA Table 1 tasks and the effectiveness of dust controls, the contribution of background silica dust to personal exposures, and the use of a photometric instrument to assess silica dust exposure in real time" - Cothern, Emily J., author; Brazile, William, advisor; Reynolds, Stephen, committee member; Autenrieth, Daniel, committee member; Fisher, Gwen, committee member (Colorado State University. Libraries, 2021)
To view the abstract, please see the full text of the document.
Exposure to respirable crystalline silica during five OSHA Table 1 tasks and the effectiveness of dust controls, the contribution of background silica dust to personal exposures, and the use of a photometric instrument to assess silica dust exposure in real time
Keywords: dust control effectiveness; photometric instrument; respirable crystalline silica correction factor; OSHA Table 1; background silica dust; respirable crystalline silica